2017
DOI: 10.1007/s11433-017-9012-8
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion relation and surface gravity of universal horizons

Abstract: In Einstein-aether theory, violating Lorentz invariance permits some super-luminal communications, and the universal horizon can trap excitations traveling at arbitrarily high velocities. To better understand the nature of these universal horizons, we first modify the ray tracing method, and then use it to study their surface gravity in charged Einstein-aether black hole spacetime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…But, for charged black holes, such a generalization is still absent [242]. Recent investigations [245][246][247] with a more general dispersion relation showed that both of the temperature and surface gravity obtained by considering peering behavior of rays near the universal horizons depend on the parameter z, which characterizes the leading order k 2z of the dispersion relation [cf. Eqs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, for charged black holes, such a generalization is still absent [242]. Recent investigations [245][246][247] with a more general dispersion relation showed that both of the temperature and surface gravity obtained by considering peering behavior of rays near the universal horizons depend on the parameter z, which characterizes the leading order k 2z of the dispersion relation [cf. Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more careful studies of ray trajectories showed that the surface gravity for particles with a nonrelativistic dispersion relation (3.1) is given by [246],…”
Section: )mentioning
confidence: 99%
“…When z = 2 it reduces to the case considered in [25,26]. Recently, more careful studies of ray trajectories showed that the surface gravity for particles with a general nonrelativistic dispersion relation is given by [30,31],…”
Section: Introductionmentioning
confidence: 99%
“…But, in more general cases, both of them will depend on z, as shown by Eq. (4.43), although the standard relation, T z≥2 U H = κ z≥2 U H /(2π), is still expected to hold [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more careful studies of ray trajectories showed that the surface gravity for particles with a nonrelativistic dispersion relation is indeed given by [39],…”
Section: Introductionmentioning
confidence: 99%